Simulation-based Analysis of 20 kW PV System - Atta Ur Rehman; Imtiaz Ahmad (Pakistan Journal of Engineering & Technology)
Nowadays, due to rising environmental degradation and declining use of traditional energy sources. Renewable energy sources were the finest alternative and solution because it is currently necessary to produce energy from sources that are environmentally friendly and don't deplete. Among them, the wind and sun are well-known energy sources. However, solar is the finest option because of its advantages over other sources, such as its enriching energy source and abundance. This research focuses on standalone PV systems that employ batteries as a backup power source. To overcome this unpredictability and make the system linear for this purpose, we used nickel metal hydride batteries. As we know, the PV system is extremely reliant on the outside environment and climate, thus it can provide less electricity during the night or in cold weather. It is the greatest since it is widely available, inexpensive, and used in air and solar power systems as well as high-powered appliances. For managing a standalone PV system, the Simulink model is crucial. Batteries and a PV system that correspond to one another are employed. To get the most power out of the solar panel under the circumstances, algorithms like MPPT are applied. MPPT also regulates the current supplied to the battery. By boosting the PV panel's duty cycle, a boost converter is utilized to raise the level of DC voltage it produces. To run the single-phase appliances, a suitable AC output with an equivalent frequency and amplitude is provided by an inverter.  The model was created using MATLAB and Simulink, and the results demonstrate that it achieves the goals of a PV standalone system.